HLTCOE Participation at TAC 2013 - McNamee, Paul; Finin, Tim; Lawrie, Dawn; Mayfield, James (My University, 2013)
The JHU HLTCOE participated in the Entity Linking and Cold Start Knowledge Base tasks in this year’s Text Analysis Conference Knowledge Base Population evaluation. We have previously participated in TAC-KBP evaluations in 2009, 2010, 2011, and 2012. Our primary focus this year was on the Cold Start task; improvements to our existing KELVIN system included consolidating slot values for an entity, removal of suspect intra-document conference chains, streamlined cross-document entity coreference, and application of inference rules to expand the number of asserted facts.
Cold Start task: improvements to our existing KELVIN system
Keywords: HLTCOE; Entity Linking; Cold Start Knowledge Base; KELVIN; UMBC Ebiquity Research Group